2022
DOI: 10.12659/msm.937146
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin/Red Blood Cell Distribution Width Ratio in Peripheral Blood Is Positively Associated with Prognosis of Patients with Primary Hepatocellular Carcinoma

Abstract: Background The prognostic value of the hemoglobin/red blood cell distribution width ratio in primary hepatocellular carcinoma remains unknown. This study aimed to analyze the correlation between hemoglobin/red blood cell distribution width ratio and hepatocellular carcinoma prognosis. Material/Methods Medical records of hepatocellular carcinoma patients were analyzed retrospectively. The hemoglobin/red blood cell distribution width ratio cut-off value was determined as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 41 publications
0
18
0
2
Order By: Relevance
“…HCC is one of the most vascular solid tumors, where several studies have shown anemia as a consequence of cytokine-mediated disorder, leading to reduced cell production, the rate of blood flow, microcirculation, and hemoglobin (Hb) concentration. 45 Thus, an important factor for the worsened prognosis of HCC is lower Hb levels could be due to the tumor hypoxia caused by anemia. The present study found that the oxygen–hemoglobin interaction, and various cellular events such as an oxidative cell environment and cell viability, are related to differences in the optical absorption spectra of whole blood where different absorption bands, such as the Soret band (417–420 nm), β and α, and the absorption valley at 513 nm.…”
Section: Resultsmentioning
confidence: 99%
“…HCC is one of the most vascular solid tumors, where several studies have shown anemia as a consequence of cytokine-mediated disorder, leading to reduced cell production, the rate of blood flow, microcirculation, and hemoglobin (Hb) concentration. 45 Thus, an important factor for the worsened prognosis of HCC is lower Hb levels could be due to the tumor hypoxia caused by anemia. The present study found that the oxygen–hemoglobin interaction, and various cellular events such as an oxidative cell environment and cell viability, are related to differences in the optical absorption spectra of whole blood where different absorption bands, such as the Soret band (417–420 nm), β and α, and the absorption valley at 513 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Our study expands this scope to include a broader demographic of patients with sepsis, diverging from the narrower focus on those with AF or SAE. Prior research has associated low HRR levels with decreased long-term survival in individuals with cancer or heart disease,13 14 19–21 suggesting that HRR at ICU admission might serve as a novel prognostic indicator for patients who are critically ill. Furthermore, our RCS analysis demonstrates a non-linear association between HRR and all-cause mortality, indicating that mortality rates decline with increasing HRR up to a threshold of 7.22, beyond which HRR does not influence mortality rates.…”
Section: Discussionmentioning
confidence: 99%
“…The HRR is a prognostic marker for various malignant tumors [17][18][19][20][21]. In a meta-analysis by Chi et al, a low HRR was associated with an increased risk of all-cause mortality (hazard ratio [HR] 2.29) and disease progression or relapse (HR 2.19).…”
Section: Discussionmentioning
confidence: 99%
“…Red cell distribution width (RDW) predicts ovarian cancer (OC) with an SE and SP of 76.7% and 70.3%, respectively [16]. Recently, the Hb-to-RDW ratio (HRR) has been reported to be a prognostic marker for malignant tumors, including head and neck cancer, lung cancer, esophageal cancer, gastric cancer, hepatoma, renal cell carcinoma, bladder cancer, and malignant lymphoma [17][18][19][20][21]. Additionally, the diagnostic efficacy of HRR for breast, nasopharyngeal, and lung cancers has been reported [17,22,23].…”
Section: Introductionmentioning
confidence: 99%